Uterine Rupture on MRI Presenting as Nonspecific Abdominal Pain in a Primigravid Patient with 28-Week Twins Resulting in Normal Neurodevelopmental Outcomes at Age Two - Kathryn L. Ponder; Rosa Won; Laurel Clymer (Case Reports in Obstetrics and Gynecology)
Background. Uterine rupture is a rare occurrence that requires a high index of suspicion, particularly in a primigravid patient who presents prior to the onset of labor. Mortality rates are particularly high in primigravid patients. Case. A 36-year-old gravida 1, para 0 patient with dichorionic diamniotic twins presented at 28-weeks of gestation with abdominal pain. The pain was initially intermittent and felt to be musculoskeletal in origin. Ultrasound imaging after 3 days of worsening abdominal pain revealed extrauterine fluid, prompting an urgent MRI. MRI diagnosed the uterine rupture with hemoperitoneum and herniation of both amniotic sacs outside of the uterus, including one twin’s torso and extremities, prompting emergency cesarean section. The premature twins required 2-month hospitalizations and had no neurodevelopmental impairments at 2-year follow-up. Conclusion. We present a unique case of rupture of an unscarred uterus in a primigravid patient prior to the onset of labor. Multiple gestation is a risk factor. This report adds to a handful of cases in which a history of endometriosis or extrauterine pelvic surgery was also present. The use of ultrasound and MRI to evaluate nonspecific abdominal pain led to the diagnosis and survival of both the mother and her premature twins.